Analisis Kebijakan Program Sekolah Menengah Kejuruan Pusat Keunggulan (SMK PK) di Indonesia dengan CIPP - Dedy Yusuf Aditya; Gita Kencanawaty (Jurnal Bintang Manajemen, 2024)
Education plays a central role in nation-building, with Vocational High Schools (SMK) in Indonesia holding a crucial role in providing skilled workforce. This article analyzes the policy of the Center of Excellence Vocational High School Program (SMK PK) using the Context, Input, Process, Product (CIPP) approach and a qualitative research method through library research analysis. The evaluation is based on legal foundations, objectives, curriculum implementation, resources, learning processes, and the impact of the SMK PK program. Context analysis reveals a strong legal foundation, yet improvement is needed in socialization and training. Input evaluation appreciates an industry-aligned curriculum design, although challenges persist in human resources and infrastructure. The curriculum implementation process shows progress, but coordination and synchronization need enhancement. Overall, the SMK PK program has a positive impact, improving graduate quality and fostering synergy between SMK, industry, and government. Challenges such as assistance focus, job market mismatch, and a lack of productive subject teachers require further attention. In conclusion, a comprehensive evaluation of the SMK PK program provides a complex overview, highlighting the potential to enhance vocational education quality in Indonesia.